Non-degenerate maximum principle for optimal control problems with discontinuous right-hand side. (2nd January 2020) - Kostyukova, O. I.; Dudina, O. S.
ABSTRACT: In the paper, optimal control problems with discontinuous right-hand side are considered. The main attention is paid to situations when there are intervals where optimal trajectory lies on a switching surface. It is shown that for such a situation the known optimality conditions degenerate: they are satisfied for any feasible control. Hence such conditions are not informative. New non-degenerate necessary optimality conditions in a form of Maximum principle are formulated and proved. Comparison of the obtained optimality conditions with ones known from the literature is presented.